Dystrofia żółtkowata dołkowo-plamkowa dorosłych – opis przypadku - Kłosowska-Zawadka, Anna; Bernardczyk-Meller, Jadwiga (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: Adult onset vitelliform macular dystrophy (AVMD) was first reported by Gass in 1974. This paper presents rare case of AVMD, in 3 years course of observation. Material and methods: Visual acuity of R.E. was 0.1 with metamorphopsias in Amsler-test., of L.E. was 1.0 sc. The metamorphopsias in LE were first noticed 3 years later. In ophthalmoscopy in LE typical a vitelliform-like macular lesion was seen, in RE faded vitelliform changes and the RPE atrophy around it. FA of RE showed typical hypofluorescent spot in the center of the macula with small hyperfluorescent spots around it, called corona sign. The same changes in FA of the LE were first noticed 3 years later. The OCT showed central thickening in the reflective band representing RPE in both eyes. The ERG and EOG results were normal. Conclusions: The ophthalmoscopic appearance of the AVMD is very similar to that in Best’s disease. In our case the correlation between appearance of metamorphoses and changes in AF was presented